Introdução aos territórios produtores de gemas: o caso brasileiro do nordeste de Minas Gerais - Aurélien Reys (Confins)
The purpose of this chronicle is to present activities and actors involved in gemstone exploitation in the Northeastern part of the brazilian state of Minas Gerais. Considered to be one of the largest precious stones reserve in the world, the area offers therefore a perfect opportunity for further understanding on such industry